Streetwise e-commerce : establish your online business, expand your reach, and watch your profits soar! - Risdahl, Aliza (Avon, Mass. : Adams Media, 2007)
Offers tools, strategies, and knowledge for maximizing a business' presence on the Internet.
"The small business solution"--Cover.
Includes bibliographical references and index.
Keywords: Electronic commerce